RSA-based partially blind signature with low computation - Hung-Yu Chien; Jinn-Ke Jan; Yuh-Min Tseng (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
With a partially blind signature scheme, the signer inoculates non-removable common information into his blind signature. This common information may represent the date or the amount of cash. Due to its untraceability and partial blindness property, the partially blind signature plays an important role in many e-commerce applications. Based on the RSA scheme, we propose a partially blind signature with low computation which makes it attractive for mobile client and smart-card implementation.